A case of primary vasoproliferative tumor with full-thickness macular hole - Rishi, Pukhraj; Sreenivasan, Janani (GMS Ophthalmology Cases, 2022)
A 53-year-old female presented with defective vision in the left eye of one week duration with a best-corrected visual acuity (BCVA) of 6/9. Fundus examination showed a primary retinal vasoproliferative tumor (RVPT) at the inferotemporal quadrant and a small full-thickness macular hole (MH). The patient underwent cryotherapy for RVPT, followed later by vitrectomy with internal limiting membrane peeling and gas tamponade. The tumor regressed and the MH was closed with BCVA of 6/9. RVPT can present with remote macular complications like epiretinal membrane, cystoid macular edema, macular exudates, and rarely full-thickness MH. Management should be directed towards the tumor as well as the complication.